Aplicación de ultrasonido y sus técnicas en endodoncia - Camacho Torres, Katherin Mishell (2022)
ABSTRACT: Ultrasound, being ultrasonic energy, has vibrations of 2-20 MHz with the advantages of being minimally invasive, low cost and a fast method, and in the endodontic area it has multiple applications that have been proven for many years. The present bibliographic review was carried out with the purpose of expanding the knowledge on the uses of ultrasound in endodontics. A literature search was carried out, extracted from databases such as PubMed, ResearchGate, Science Direct; during the period from 2009 to 2021. Through exclusion and inclusion criteria, considering as quality aspects the average citation count (ACC), impact factor of the journal in which the article is published through Scimago Journal Ranking (SJR), once the selection stage was applied, a total of 66 articles were obtained for the systematic review. In addition, the GRADE Pro application was used to validate the different treatments and applications of ultrasound based on the evidence. The results showed that ultrasound in endodontics has various applications from diagnosis using the ultrasonograph to differentiate various pathologies at the periapical level, likewise it is used with great effectiveness in endodontic irrigation and removal of microorganisms, ultrasound is a very useful instrument to remove broken instruments in the canal system, the versatility was evidenced through evidence-based dentistry.